PHILOSOPHICAL DISCOURSE OF A POSTMODERN: UNIVERSITY'S IDEA IN CLASSICAL AND NONCLASSICAL DIMENSION - Лебідь, А. Є. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The evolutions of University's idea in classical and nonclassical (postmodern) interpretations are analyzed in this article. Prospects of development of University in an information society, its primary goals are discussed.